Model Kandidasi Birokrat oleh Partai Politik pada Pemilihan Kepala Daerah Langsung di Kabupaten Rokan Hilir Tahun 2015 - Amir Syamsuadi; MHD Rafi Yahya (Universitas Sultan Ageng Tirtayasa, 2018)
This research wants to know the model candidacy, and motive political party choose the candidate with bureaucrat background in head election government in Rokan Hilir Regency year 2015. This study uses a qualitative approach; Triangulation technique was operated to get the more in-depth analysis to give about model candidacy and motives political party to chose the candidate with background bureaucrat. The results show that the bureaucrat candidacy model by political parties with the mechanism of selection, classification, and recommendation of candidates. The motive of the political party choose bureaucrat background candidates on the direct local head election implementation in Rokan Hilir Regency in the year 2015 is based on several aspects, First, the agreement of support through bargaining and political contracts. Second, the social status and governance management capability. Third, financial sponsor and electability network. Fourth, the weakness of the system of cadres in the political party. Fifth, bureaucracy mobilization capability.Keywords: Model, Candidacy, Political Party, Direct Local Government Election, Rokan Hilir Regency.